Edukasi Pembelajaran Matematika Pada Sekolah Dasar Menggunakan Animasi Interaktif - Tri Santoso; Adelia Alvi Yana; Syahriani - STMIK Nusa Mandiri; Astrilyana - UBSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2020)
Abstract - Learning is a process of creating an environment that allows the learning process. Learning in terms of the activities of students in interacting with the environment that results in changes in behavior that is constant. Many applications are made to help students understand the subject matter. In teaching and learning activities computer technology plays an especially important role in mathematics can help students to be more enthusiastic in learning these math subjects. Mathematics is one branch of science which can be said to be the basis of knowledge because it contains logic. With the construction of interactive media based on animated mathematics learning, it is possible that teaching and learning activities in schools are more interesting, especially for elementary school students. Therefore, with the interactive learning media animation is expected to help students in school in learning mathematics. The background of this study aims to develop abilities and attract students in learning mathematics both at school and at home, specifically learning flat building space using Adobe flash animation in grade 5 elementary school. By making this multimedia-based learning application design, starting from the initial stages, namely interviews, observation, distribution of questionnaires and making the evaluation results. Then also proceed with making the animation program design using Adobe Flash CS 5. As a multimedia-based application, learning becomes more fun and can also be an interest in learning motivation for students. Keywords: Mathematics Learning, Interactive, Animation Abstraksi - Pembelajaran adalah suatu proses penciptaan lingkungan yang memungkinkan terjadinya proses belajar. Belajar dalam pengertian aktivitas dari peserta didik dalam berinteraksi dengan lingkungan yang menghasilkan perubahan perilaku yang bersifat konstan. Banyak aplikasi yang dibuat untuk membantu para siswa memahami materi pelajaran. Dalam kegiatan belajar mengajar teknologi komputer sangat berperan khususnya dalam mata pelajaran matematika dapat membantu para siswa untuk lebih bersemangat dalam mempelajari mata pelajaran matematika tersebut. Matematika merupakan salah satu cabang ilmu yang dimana dapat dikatakan sebagai dasar ilmu karena didalamnya mengandung ilmu logika. Dengan dibangunnya media interaktif pembelajaran matematika berbasis animasi ini memungkinkan dalam kegiatan belajar mengajar disekolah lebih menarik, khususnya untuk siswa sekolah dasar. Oleh sebab itu dengan adanya media interaktif pembelajaran animasi diharapkan dapat membantu para siswa di sekolah dalam belajar matematika. Latar belakang penelitian ini bertujuan untuk mengembangkan kemampuan dan menarik siswa dalam belajar matematika baik disekolah maupun dirumah, khususnya pembelajaran ruang bangun datar dengan menggunakan animasi Adobe flash di kelas 5 SD. Dengan membuat rancangan aplikasi pembelajaran berbasis multimedia ini, dimulai dari tahap awal yaitu wawancara,obsevarsi, pembagian kuisioner dan membuat hasil evaluasi. Kemudian juga dilanjutkan dengan membuat rancangan program animasinya dengan menggunakan Adobe Flash CS 5. Sebagai aplikasi berbasis multimedia, belajar menjadi lebih menyenangkan dan dapat menjadi minat juga motivasi belajar untuk siswa. Kata Kunci: Pembelajaran Matematika, Interaktif, Animasi